Gene Modification and Three-Dimensional Scaffolds as Novel Tools to Allow the Use of Postnatal Thymic Epithelial Cells for Thymus Regeneration Approaches. (29th May 2019) - Bortolomai, Ileana; Sandri, Monica; Draghici, Elena; Fontana, Elena; Campodoni, Elisabetta; Marcovecchio, Genni Enza; Ferrua, Francesca; Perani, Laura; Spinelli, Antonello; Canu, Tamara; Catucci, Marco; Di Tomaso, Tiziano; et al.
Abstract: Defective functionality of thymic epithelial cells (TECs), due to genetic mutations or injuring causes, results in altered T-cell development, leading to immunodeficiency or autoimmunity. These defects cannot be corrected by hematopoietic stem cell transplantation (HSCT), and thymus transplantation has not yet been demonstrated to be fully curative. Here, we provide proof of principle of a novel approach toward thymic regeneration, involving the generation of thymic organoids obtained by seeding gene-modified postnatal murine TECs into three-dimensional (3D) collagen type I scaffolds mimicking the thymic ultrastructure. To this end, freshly isolated TECs were transduced with a lentiviral vector system, allowing for doxycycline-induced Oct4 expression. Transient Oct4 expression promoted TECs expansion without drastically changing the cell lineage identity of adult TECs, which retain the expression of important molecules for thymus functionality such as Foxn1, Dll4, Dll1, and AIRE. Oct4-expressing TECs (iOCT4 TEC) were able to grow into 3D collagen type I scaffolds both in vitro and in vivo, demonstrating that the collagen structure reproduced a 3D environment similar to the thymic extracellular matrix, perfectly recognized by TECs. In vivo results showed that thymic organoids transplanted subcutaneously in athymic nude mice were vascularized but failed to support thymopoiesis because of their limited in vivo persistence. These findings provide evidence that gene modification, in combination with the usage of 3D biomimetic scaffolds, may represent a novel approach allowing the use of postnatal TECs for thymic regeneration. Stem Cells Translational Medicine   2019;8:1107–1122 : Abstract : Transient Oct4 expression promoted thymic epithelial cells expansion without drastically changing the cell lineage identity of adult thymic epithelial cells. iOCT4 thymic epithelial cells were able to grow into three-dimensional collagen type I scaffolds both in vitro and in vivo demonstrating that the collagen structure reproduced a three-dimensional environment similar to the thymic extracellular matrix, perfectly recognized by thymic epithelial cells. in vivo results showed that thymic organoids transplanted subcutaneously in athymis nude mice were vascularized but failed to support thymopoiesis because of the limited in vivo persistence. These findings provide evidence that gene modification, in combination with the usage of three-dimensional biomimetic scaffolds, represents a novel approach allowing the use of postnatal thymic epithelial cells for thymic regeneration.